Mathematical modeling and simulation of imperfect mixing in bioreactors - Özbek, B (KING FAHD UNIV PETROLEUM MINERALS, 1998)
In this study, a scale-down approach has been used for the simulation of imperfect mixing in growth processes by considering a configuration of two backmix flow reactors (the first one is aerated but the second one is not aerated) and one plug flow tubular reactor (not aerated). The steady-state concentrations of biomass and enzyme in a continuous culture were calculated as a function of dilution rate using modified Monod growth kinetics. A mathematical model for this combination of three bioreactors was developed to account for growth, substrate utilization (oxygen and glucose), and enzyme synthesis and decay. The model was then used to investigate biomass production and enzyme expression in relation to the recirculation ratio and the volumetric fraction of the plug flow tubular reactor, the interchange flow rate and the volume fraction of the second backmix flow reactor of the fermentation system. All these parameters were found to be significant factors in the biomass and enzyme production from the combined fermentation system. This model was also compared with some of the existing models.
Keywords: Science & Technology - Other Topics